2020
DOI: 10.1186/s12974-020-01807-3
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord NLRP1 inflammasome contributes to dry skin induced chronic itch in mice

Abstract: Background: Dry skin itch is one of the most common skin diseases and elderly people are believed to be particularly prone to it. The inflammasome has been suggested to play an important role in chronic inflammatory disorders including inflammatory skin diseases such as psoriasis. However, little is known about the role of NLRP1 inflammasome in dry skin-induced chronic itch. Methods: Dry skin-induced chronic itch model was established by acetone-ether-water (AEW) treatment. Spontaneous scratching behavior was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…Genetic variations in NLRP1 are also positively associated with a higher susceptibility to psoriasis ( 101 ). Interestingly, higher NLRP1 expression is correlated to dry skin–induced chronic itch in a sex- and age-dependent manner in mice ( 168 ). NLRP1 has recently been implicated in the pathophysiology of IBD by restricting the beneficial butyrate-producing Clostridiales in the gut of the dextran sulphate sodium (DSS)-induced colitis murine model of IBD ( 107 ).…”
Section: Inflammasomes In Chronic Inflammatory Disordersmentioning
confidence: 99%
“…Genetic variations in NLRP1 are also positively associated with a higher susceptibility to psoriasis ( 101 ). Interestingly, higher NLRP1 expression is correlated to dry skin–induced chronic itch in a sex- and age-dependent manner in mice ( 168 ). NLRP1 has recently been implicated in the pathophysiology of IBD by restricting the beneficial butyrate-producing Clostridiales in the gut of the dextran sulphate sodium (DSS)-induced colitis murine model of IBD ( 107 ).…”
Section: Inflammasomes In Chronic Inflammatory Disordersmentioning
confidence: 99%
“…The NLRP1 inflammasome is extensively expressed in central nervous system, particularly in neurons and serves as a platform for the recruitment of the apoptosis-associated speck-like protein containing a card (aSc) and procaspase-1 protease. once activated, aSc activates caspase-1 and then induces the processing and maturation of the il-1β, il-6 and il-18 (59). Previous studies have shown that NLRP1 inflammasome is upregulated and accompanied by neuronal damage and cognitive decline in mice model of ad (15).…”
Section: Discussionmentioning
confidence: 99%
“…24 A previous study reported that the spinal cord NOD-like receptor family pyrin domain containing 1 (NLRP1) inflammasome-mediated inflammatory response contributes to dry skin–induced chronic pruritus via the transient receptor potential vanilloid 1 channel and plays an important role in pruritic transmission. 25 NLRP3 belongs to the same family as NLRP1. In addition, increasing evidences show that inflammatory cytokines such as TNF-α, IL-1β and IL-18 are involved in chronic pruritus.…”
Section: Discussionmentioning
confidence: 99%